ANALISIS PELAKSANAAN FUNGSI MANAJEMEN KOPERASI OLEH PENGURUS KPRI SMANSA JAYA SMAN 1 SUNGAI AMBAWANG - Astuti, Sri Puji; Khosmas, F Y; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research originated from the problem "The implementation of cooperative management functions by administrators of the Republic of Indonesia Employee Cooperative (KPRI) Smansa Jaya in SMAN 1 Sungai Ambawang". With the sub-problems in this study are (1) How is the implementation of the cooperative management planning function by the management of KPRI Smansa Jaya?; (2) How is the implementation of the cooperative management organizing function by the management of KPRI Smansa Jaya?; (3) How is the implementation of the cooperative management actuating function by the management of KPRI Smansa Jaya?; and (4) How is the implementation of the cooperative management controlin gfunction by the management of KPRI Smansa Jaya?. The method used in this study is a descriptive method with a survey research form. As for the source of data in this study are management, supervisors and members of cooperatives. Data is collected using interview instruments, observations, and supporting documents. Based on the results of interviews and observations shows that the implementation of the cooperative management function by the KPRI Smansa Jaya board is good enough. This can be seen from the ability of the management in carrying out the management function of the cooperative, so that members feel satisfied with the performance of the board in providing services and in managing cooperatives to continue expected by the members of the cooperative.Â Keywords: Cooperative Management Functions, Management Of Cooperative, Administrator Of Cooperatives